A Multimodal Discourse Analysis of American Restaurant Chains Instagram Post during Pandemic - Kaisar Kautsar; Muhammad Rayhan Bustam (STKIP PGRI Tulungagung, 2021)
During this pandemic situation, food companies are using their Instagram account not only to promote their products and services to stay in business but also to tell the consumer of their products to keep minimalize physical contact to help in this horrible situation. In this study, there were 3 (three) Instagram post from 3 (three) different companies which are in food business that were analyse through multimodal analysis. The purpose of this study was to found out what visual and verbal were being used in those companies Instagram post during this pandemic period and what message they brought through their Instagram post. This study was implemented descriptive qualitative method and interactive metafunction by Kress and van Leeuwen and interpersonal metafunction by Halliday. The writer concluded that in this study those companies not only trying to sell and advertise their products and services but also to suggest their consumer to minimalize physical contact during this pandemic situation.